1977
DOI: 10.4039/ent109165-2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TEMPERATURE ON DEVELOPMENTAL RATE AND FECUNDITY OF THE PEAR PSYLLA, PSYLLA PYRICOLA (HOMOPTERA: PSYLLIDAE)

Abstract: Can. Ent. 109: 165-169 (1977) At constant temperatures between 10.0" and 32.2"C with 16 h photoperiod development of eggs and nymphs was slowest at 10.0" (61.8 days av.) and most rapid at 26.7OC (27.0 days av.). Mortality of eggs and nymphs was moderate (43.78) at 10.OO, least (24.2%) at 21.1°, and 100% at 32.2"C. Between 15.6" and 35.0°C, 16 h photoperiod, fecundity of winter form adults was greatest (486.3 eggs av.) at 15.6" and lowest (0.0 eggs) at 35.0QC. For summer form adults fecundity was moderate (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Several fenoxycarb-treated females each deposited more than 1900 eggs and survived more than 3 months in the laboratory, providing no indication that overwintering with mature ovaries caused a reduction in these two fitness characteristics. It is of some interest to note that means for both measurements are considerably higher than those obtained for a population of winterform psylla in Canada (McMullen & Jong, 1977; fecundity = 300 eggs per female; longevity = 38 days [at 21 ~ We have no explanation for the differences between the two studies.…”
Section: Discussionmentioning
confidence: 71%
“…Several fenoxycarb-treated females each deposited more than 1900 eggs and survived more than 3 months in the laboratory, providing no indication that overwintering with mature ovaries caused a reduction in these two fitness characteristics. It is of some interest to note that means for both measurements are considerably higher than those obtained for a population of winterform psylla in Canada (McMullen & Jong, 1977; fecundity = 300 eggs per female; longevity = 38 days [at 21 ~ We have no explanation for the differences between the two studies.…”
Section: Discussionmentioning
confidence: 71%
“…Observations by Kapatos and Stratopoulou (1999) of C. pyri egg development under orchard conditions specify longer development times and a lower threshold (2.31 °C), the caveat being that they related developmental rates to average temperature during observation periods. McMullen and Jong (1977) published data for C. pyricola showing unlikely thermal thresholds below 0 °C. Therefore, our results seem more reliable than literature data.…”
Section: Termination Of Reproductive Diapausementioning
confidence: 99%
“…The present study suggests that the winter‐form psyllids have a good tolerance of high temperature because, under the extreme condition of constant 35°C, they could still reproduce well, similar to summer‐form individuals (327 and 349 eggs, respectively). In contrast, M c M ullen and Jong (1977) found that winter‐form C. pyricola reproduced during the cold and cool weather of early spring, but at temperatures above 30°C the number of eggs laid was reduced to zero. The adaptation of both forms of A. pistaciae to a wide range of temperature and their high reproductive capability are considered as important features, particularly for the winter‐forms, so that they can establish a very large colony from late March.…”
Section: Discussionmentioning
confidence: 78%